Enhancement of mechanical properties of vertically aligned carbon nanotube arrays due to N+ ion irradiation. (27th April 2020) - Jarząbek, Dariusz M; Harvey, Cayla; Levintant-Zayonts, Neonila; Wojciechowski, Tomasz; Gniadek, Marianna; Krajewski, Marcin; Pathak, Siddhartha
Abstract: In this work we apply N + ion irradiation on vertically aligned carbon nanotube (VACNT) arrays in order to increase the number of connections and joints in the CNT network. The ions energy was 50 keV and fluence 5 × 10 17 ions cm −2 . The film was 160 μ m thick. SEM images revealed the ion irradiation altered the carbon bonding and created a sponge-like, brittle structure at the surface of the film, with the ion irradiation damage region extending ∼4 μ m in depth. TEM images showed the brittle structure consists of amorphous carbon forming between nanotubes. The significant enhancement of mechanical properties of the irradiated sample studied by the cyclic nanoindentation with a flat punch indenter was observed. Irradiation on the VACNT film made the structure stiffer, resulted in a higher percentage recovery, and reduced the energy dissipation under compression. The results are encouraging for further studies which will lead to create a class of materials—ion-irradiated VACNT films—which after further research may find application in storage or harvesting energy at the micro/nanoscale.